2007
DOI: 10.1002/elan.200703937
|View full text |Cite
|
Sign up to set email alerts
|

Double Elimination Voltammetry of Short Oligonucleotides

Abstract: In connection with adsorptive stripping (AdS) technique, elimination voltammetry with linear scan (EVLS) in double mode was successfully employed in the analysis of homo-ODNs: 5'-AAA AAA AAA-3' (dA 9 ) and 5'-CCC CCC CCC-3' (dC 9 ), and hetero-ODNs: 5'-CCC AAA CCC-3' (H3), 5'-CAC CAC CAC-3' (H4), and 5'-ACC CAC CCA-3' (H9) on hanging mercury drop electrode (HMDE). Analogously to single EVLS function E4 (conserving the diffusion current I d and eliminating kinetic and charging currents I k , I c ) for the elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…AdS in combination with elimination voltammetry with linear scan (EVLS) was shown to resolve overlapping reduction peaks of C and A by eliminating kinetic and charging currents, while conserving the diffusion current. EVLS was applied for studies involving not only short ODNs, but also chromosomal DNAs . A heptamer d­(GCGAAGC), forming a stable hairpin-like structure, was also studied by EVLS and was detected down to 2 nM concentration .…”
Section: Reduction Oxidation and Adsorption Of Nucleic Acids At Elect...mentioning
confidence: 99%
“…AdS in combination with elimination voltammetry with linear scan (EVLS) was shown to resolve overlapping reduction peaks of C and A by eliminating kinetic and charging currents, while conserving the diffusion current. EVLS was applied for studies involving not only short ODNs, but also chromosomal DNAs . A heptamer d­(GCGAAGC), forming a stable hairpin-like structure, was also studied by EVLS and was detected down to 2 nM concentration .…”
Section: Reduction Oxidation and Adsorption Of Nucleic Acids At Elect...mentioning
confidence: 99%
“…Several papers have been devoted to hairpinforming ODNs [12] and studies focused on DNA-mediated charge transfer [13]. Results of some quite recent studies showed that the behavior of ODNs at the mercury and amalgam electrodes is strongly dependent on their nucleobase composition (especially when a specific nucleobase or nucleobase type strongly prevails) [14] and nucleotide sequence (especially when it is non-random) [12,[15][16][17][18]. Grich ODNs have recently been studied by voltammetric methods at a glassy-carbon electrode in combination with atomic-force microscopy [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The shape of this signal was calculated theoretically and the theoretical ratio of peak to peak-counterpeak height corresponds to 0.4097 [29]. This fact initiated the application of the adsorptive transfer stripping (AdS) technique together with EVLS for the analysis of oligonucleotides, including hairpins [27,30,31]. It was found that AdS EVLS was able to separate overlapped voltammetric peaks and to indicate quickly the adsorbed state of depolarizers.…”
Section: Introductionmentioning
confidence: 99%